Spiritualitas Humanum: Penghargaan Martabat Kaum Perempuan di Institusi Pendidikan Tinggi Katolik - Karyanto, Andrian Widi; Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2022)
An institution of Catholic higher education as an academic community is tasked with protecting and respecting the dignity of human life. It has an institutional autonomy to carry out its functions and guarantee its members a freedom based on the values of truth, justice, equality, and general welfare. Its vision leads to the formation of a community that is authentically human (humanum) and imbued with the spirit of Christ. Everyone involved in this higher education is inspired by the Christian principles and therefore is encouraged to live out their Christian calling in a mature and responsible manner. Catholic higher education as part of the Church must give a space for spiritual life assistance for young people who are studying in the institution. Furthermore, it should pay attention to all the problems and the needs of the students today, especially those concerning the human dignity. This article proposes a spirituality of humanum practised in a Catholic university as a framework for higher education in order to respect the dignity of women and men involved in the institution. In this framework, all individuals in the campus may increasingly experience acceptance and respect for their human dignity as noble image of God may live in accordance with the Christian values.